A case report of pediatric acute lymphoblastic leukemia with e8a2 BCR/ABL1 fusion transcript - Aleksandra Mroczkowska; Bożena Jaźwiec; Justyna Urbańska-Rakus; Sylwia Szymanowska; Anna Tessmann; Sonia Pająk; Katarzyna Machnik; Olga Haus; Tomasz Wróbel (BMC, 2022)
Abstract Background Acute lymphoblastic leukemia is the most common type of cancer in children. Most often it affects the age group between 2 and 5 years of age. Studies have shown an improvement in general survivability, more than 90% 5-year overall survival (OS). Current treatment protocols for acute lymphoblastic leukemia require verification of the presence of favorable and unfavorable genetic abnormalities, which help qualify patients to the appropriate risk group and select a more suitable treatment. The presence of the BCR/ABL1 fusion gene stratifies the patient into a high-risk group and requires special treatment with tyrosine kinase inhibitors (TKI). The three dominant mRNA transcripts are e1a2, e13a2, and e14a2. Nevertheless, cases of atypical BCR/ABL1 transcripts have also been reported. Case presentation This paper presents the case of a pediatric patient with Ph + B-cell precursor acute lymphoblastic leukemia with rare atypical e8a2 BCR/ABL1 fusion transcript. Our patient achieved complete remission after 33 days of treatment. Molecular and cytogenetic studies in TP1 did not reveal the presence of the BCR/ABL1 transcript. The PCR-MRD test in TP1b was negative, the patient did not require hematopoietic stem cell transplantation. Conclusion Genetic evaluation of the bone marrow sample is crucial in the initial stage of the diagnosis. Fluorescent in situ hybridization and reverse transcriptase polymerase chain reaction with Sanger sequencing are the appropriate methods used in the detection of rare variants of BCR/ABL1 transcripts.